2016
DOI: 10.3390/magnetochemistry2040039
|View full text |Cite
|
Sign up to set email alerts
|

Strain Engineering of the CeNi5 System

Abstract: Abstract:The effect of strain on the CeNi 5 system has been investigated using density functional theory (DFT). The studies have shown that localised Ce 4f and Ni 3d states carry the magnetic moment of the material. The Ce 4f moment remains relatively unchanged during strain whereas the Ni 3d moment increases as the strain becomes increasingly tensile in both the basal and non-basal directions. A significant strain-dependent interaction exists between delocalised, non-magnetic Ce 6s-Ni 4s states. A weaker grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The magnetism increased as the strain becamei ncreasingly tensile and was accompanied by charget ransfer between the magnetic quantum number-resolved dorbitals. Investigations of strain-induced changes in the magnetisation of alloys have also been performed on rare-earth alloys.S tudies of the CeNi 5 system [10] have shown that the magnetism of the alloy is carried by the Ce fa nd Ni ds tates. However,u nder strain, the spin moment associated with the Ni ds tates changes far more significantly than those associate with the Ce fs tates.…”
Section: Characterisation Of the Pt-alloy Bulk And Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The magnetism increased as the strain becamei ncreasingly tensile and was accompanied by charget ransfer between the magnetic quantum number-resolved dorbitals. Investigations of strain-induced changes in the magnetisation of alloys have also been performed on rare-earth alloys.S tudies of the CeNi 5 system [10] have shown that the magnetism of the alloy is carried by the Ce fa nd Ni ds tates. However,u nder strain, the spin moment associated with the Ni ds tates changes far more significantly than those associate with the Ce fs tates.…”
Section: Characterisation Of the Pt-alloy Bulk And Surfacementioning
confidence: 99%
“…Investigations of strain‐induced changes in the magnetisation of alloys have also been performed on rare‐earth alloys. Studies of the CeNi 5 system have shown that the magnetism of the alloy is carried by the Ce f and Ni d states. However, under strain, the spin moment associated with the Ni d states changes far more significantly than those associate with the Ce f states.…”
Section: Introductionmentioning
confidence: 99%